Pencirian Produksi Amilase oleh Saccaromyces cerevisiae W303A Rekombinan - Thontowi, Ahmad; Puspaningsih, Ni Nyoman Tri; Hadi, Sofjan; Purkan, Purkan; Irawan, Bambang (JURNAL BIOLOGI INDONESIA, 2002)
ABSTRACTCharacterization of Amylase Production by Saccharomyces cerevisiae W303A Recombinants. Cloning of amylase gene from Endomycopsis fibuligera ITB.R.cc.64 into S. cerevisiae W303a can effectively increase the yeast function to digest starch directly into ethanol. Production of amylase by S. cerevisiae W303a recombinants (I and P) were done by growing in yeast peptone starch (YPS) medium. The result showed that the recombinants could be produced of amylase by gave clear zone after staining by iodium vapor. The optimum condition of production of amylase by S. cerevisiae W303a recombinants were pH 7.0, 40?C temperature incubation, and gave maximum activity after 36 hours incubation. Amylase activity of I was higher than P recombinant for these condition respectively.Key words: Characterization, amylase, S. cerevisiae W303a